2016
DOI: 10.1038/srep28038
|View full text |Cite
|
Sign up to set email alerts
|

N-cadherin is Key to Expression of the Nucleus Pulposus Cell Phenotype under Selective Substrate Culture Conditions

Abstract: Nucleus pulposus (NP) cells of the intervertebral disc are essential for synthesizing extracellular matrix that contributes to disc health and mechanical function. NP cells have a unique morphology and molecular expression pattern derived from their notochordal origin, and reside in N-cadherin (CDH2) positive cell clusters in vivo. With disc degeneration, NP cells undergo morphologic and phenotypic changes including loss of CDH2 expression and ability to form cell clusters. Here, we investigate the role of CDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
73
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 71 publications
(118 reference statements)
15
73
0
Order By: Relevance
“…N-CDH-mediated signaling is helpful to maintain a normal NP cell phenotype and NP matrix synthesis in vitro [29, 30]. In this study, N-CDH up-regulation coincided with better maintenance of the NP cell phenotype and NP matrix synthesis in the dynamic compression group.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…N-CDH-mediated signaling is helpful to maintain a normal NP cell phenotype and NP matrix synthesis in vitro [29, 30]. In this study, N-CDH up-regulation coincided with better maintenance of the NP cell phenotype and NP matrix synthesis in the dynamic compression group.…”
Section: Discussionmentioning
confidence: 53%
“…As an important molecule that is helpful to maintain a normal NP cell phenotype and NP matrix synthesis in vitro [29], results showed that N-CDH expression in the dynamic compression group was increased both at gene and protein levels compared with those in the static compression group and the control group (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth mentioning that N-CDH expression decreases with disc aging and disc degeneration and that the decrease in N-CDH expression coincides with those degenerative disc changes [15, 16]. Hence, several research teams have proposed and verified that N-CDH-mediated signaling is necessary for maintaining normal NP biology [17, 18]. In this study, high-magnitude (20% deformation) compression significantly down-regulated N-CDH expression compared with low-magnitude (2% deformation) compression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have demonstrated that N-CDH is a specific molecule that is highly expressed in normal disc NP cells compared with degenerative NP cells, adjacent disc annulus fibrosus cells and cartilage endplate cells [15, 16]. In addition, N-CDH-mediated signaling helps to maintain the normal juvenile NP phenotype and NP matrix synthesis in vitro [17, 18]. Finally, N-CDH can regulate cell behaviors, cell phenotypes and other pathological phenomena in other tissues [13, 14].…”
Section: Introductionmentioning
confidence: 99%